Expanding access to HIV treatment through community-based organizations (UNAIDS, 2005)
In 2004, the nongovernmental organization, Sidaction, with support from UNAIDS and WHO, conducted a survey of the community response to HIV treatment needs in Africa. This survey was the first attempt to map and describe the contribution made by community groups, including those founded by persons living with HIV in increasing access to antiretroviral therapy. The findings of the survey indicate that urgent and ongoing support to community-based and other nongovernmental organizations is a critical part of an effective response to HIV.
UNAIDS best practice collection
Keywords: Patient Care; organizace podporující zdraví; HIV infekce; zdravotní výchova; antiretrovirové látky; Health Care Surveys; Community Networks; Afrika; dermatovenerologie; spolupráce organizací a občanů; Health Maintenance Organizations; Anti-Retroviral Agents; péče o pacienta; Africa; průzkumy zdravotní péče; Acquired Immunodeficiency Syndrome; AIDS; HIV Infections